Effect of organic sources of nitrogen on quality and yield of Indian mustard under sodic water irrigation (Journal of Oilseed Brassica, 2026)
The groundwater in arid, and semi-arid regions used as a chief source of irrigation is generally saline/sodic,. The continuous use of such water for irrigation creates salinity or sodicity in the soil. To explore the potential of using sodic groundwater for mustard cultivation, an experiment was conducted to study the mitigation effect of organic sources of nitrogen under sodic water irrigation. The experiment comprising 24 treatment combination replicated three times, was laid out in split plot design with four treatment of sodic water (6 SAR, 10 SAR, 20 SAR, 30 SAR) and six treatment of sources of nitrogen (control, 125% RDN* through urea, 75% RDN* through urea + 50% RDN through FYM, 75% RDN through urea + 50% RDN through VC, 50% RDN through urea + 75% RDN through FYM, 50% RDN through urea + 75% RDN through VC). Results revealed that the application of 50% RDN through urea +75% RDN through VC (M5) is a better choice for mitigating adverse effect of SAR rich water on quality, and yield of mustard as the magnitude of adverse effects on quality, and yield of mustard was minimum under the application of 50% RDN through urea +75% RDN through VC (M5).Thus sodic groundwater could be a good source to exploit for supplemental irrigation through use of technology, and inputs.